1990
DOI: 10.1111/j.1440-1754.1990.tb01069.x
|View full text |Cite
|
Sign up to set email alerts
|

The value of C‐reactive protein measurement in the diagnosis of neonatal infection

Abstract: We examined whether serum C-reactive protein (CRP) measurements used in conjunction with leucocyte counts help in the diagnosis of perinatally acquired and nosocomial infections in very preterm newborn infants. One hundred and twenty-five infants born at a gestational age between 23 and 31 weeks with respiratory distress were studied at birth. A similar group of 85 infants beyond 3 days of age were also studied on 100 occasions for suspected infection. The diagnosis of proven or probable infection was correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 25 publications
3
19
0
Order By: Relevance
“…We present the results of the review of individual tests based on (1) haematological indices, (2) C reactive protein evaluation, and (3) surface swab assessment. These particular data are taken from 23 studies9 11 12 18 21-23 31 33 35 36 38-40 42 45 49 50 52 55 56 58 59and were chosen for reporting here because they relate to tests that are commonly used in clinical practice. Data on diagnostic accuracy when combinations of these tests are used are also presented; these were reported in seven studies 18…”
Section: Resultsmentioning
confidence: 99%
“…We present the results of the review of individual tests based on (1) haematological indices, (2) C reactive protein evaluation, and (3) surface swab assessment. These particular data are taken from 23 studies9 11 12 18 21-23 31 33 35 36 38-40 42 45 49 50 52 55 56 58 59and were chosen for reporting here because they relate to tests that are commonly used in clinical practice. Data on diagnostic accuracy when combinations of these tests are used are also presented; these were reported in seven studies 18…”
Section: Resultsmentioning
confidence: 99%
“…Although serum cytokine levels may rise 12 to 48 h prior to the onset of sepsis symptoms (426) and have been found to be highly predictive of neonatal sepsis, cytokine testing is not routinely performed in most clinical chemistry laboratories. Serial measurements of CRP levels appear to have the best discriminatory value for predicting septicemia among the tests currently available in many hospital laboratories, and the ability to produce CRP does not appear to be affected by gestational age (8,377,426).…”
Section: Use Of Adjunct Laboratory Tests To Predict Septicemiamentioning
confidence: 99%
“…Although serum cytokine levels may rise 12 to 48 h prior to the onset of sepsis symptoms (426) and have been found to be highly predictive of neonatal sepsis, cytokine testing is not routinely performed in most clinical chemistry laboratories. Serial measurements of CRP levels appear to have the best discriminatory value for predicting septicemia among the tests currently available in many hospital laboratories, and the ability to produce CRP does not appear to be affected by gestational age (8,377,426). Several studies have specifically addressed the utility of CRP screening in VLBW neonates, with the sensitivity of a CRP value greater than 1 mg/dl for blood culture-proven sepsis ranging from 48 to 63% when a single test is performed and from 84 to 90% when multiple CRP screens are performed over a 24-to 48-h period following onset of symptoms (77,487).…”
Section: Use Of Adjunct Laboratory Tests To Predict Septicemiamentioning
confidence: 99%
“…term infants without risk factors). The fact that for nsCRP no reference values have been established for neonates may explain the wide range of reported nsCRP sensitivities (47-100%) and specificities (6-97%) [29][30][31]. Although not as accurate, we previously had described the IL-8 lysate [13]; of all parameters tested in this study, IL-8 serum concentrations showed the highest sensitivity and specificity for EOBI within the first hours of clinical suspicion (table 1, fig.…”
Section: Crp Kinetics In Non-infected Neonatesmentioning
confidence: 99%